2009
DOI: 10.1002/ejsp.613
|View full text |Cite
|
Sign up to set email alerts
|

Ideological orientation and social context as moderators of the effect of terrorism: The case of Israeli‐Jewish public opinion regarding peace

Abstract: The study investigated the effect of severe terror attacks on Israeli-Jewish public opinion regarding peace in a context of progress toward peace (1994)(1995)(1996)(1997) compared to a context of conflict escalation (2001)(2002). We hypothesized that ideological orientations supporting peace (doves) or opposing it (hawks), as well as the social context in which terror occurs, would moderate its effects. We used the database of Peace Index polls, administered monthly to representative samples of Israeli Jews. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Some studies show that conflict‐related personal victimization predicts less outgroup tolerance (Canetti‐Nisim, Halperin, Sharvit, & Hobfoll, ), decreased forgiveness (Myers, Hewstone, & Cairns, ), and less support for legal responses to human rights violations (Elcheroth, ). However, these responses depend on other factors such as the level of violence in the community and the individual's ideological orientation (Elcheroth, ; Sharvit, Bar‐Tal, Raviv, Raviv, & Gurevich, ). Moreover, under some circumstances personal victimization may even motivate prosocial attitudes—depending on the specific meaning individuals attach to these experiences (Klar et al., ; Vollhardt, 2009b).…”
Section: Psychological Research On Collective Victimhood and Intergromentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies show that conflict‐related personal victimization predicts less outgroup tolerance (Canetti‐Nisim, Halperin, Sharvit, & Hobfoll, ), decreased forgiveness (Myers, Hewstone, & Cairns, ), and less support for legal responses to human rights violations (Elcheroth, ). However, these responses depend on other factors such as the level of violence in the community and the individual's ideological orientation (Elcheroth, ; Sharvit, Bar‐Tal, Raviv, Raviv, & Gurevich, ). Moreover, under some circumstances personal victimization may even motivate prosocial attitudes—depending on the specific meaning individuals attach to these experiences (Klar et al., ; Vollhardt, 2009b).…”
Section: Psychological Research On Collective Victimhood and Intergromentioning
confidence: 99%
“…Burundi is also a postconflict society, but it lacks such reconciliation policies. In contrast to these two postconflict settings, the eastern provinces in the DRC are experiencing ongoing violence and lack of security, which can deteriorate intergroup relations (e.g., Canetti‐Nisim et al., ; Sharvit et al., ). While the conflict in DRC cannot be clearly framed in ethnic terms as in Rwanda and Burundi (in part because there are approximately 250 ethnic groups), manipulation of ethnic tensions by leaders are an essential part of it (Autesserre, ).…”
Section: Overview Of the Present Researchmentioning
confidence: 99%
“…Previous studies conducted in the Israeli-Palestinian context have shown that the effect of terror on attitudes regarding peace varies according to ideological orientations and the transitional context in which terror occurs (Sharvit, Bar-Tal, Raviv, Raviv, & Gurevich, 2010). We were able not only to examine the impact of general conflict collective victimhood on people's support for the employment of such means during a real-time large military operation, but also to study how changes in the perception of collective victimhood affected the level of this support.…”
Section: Studymentioning
confidence: 99%
“…We were able not only to examine the impact of general conflict collective victimhood on people's support for the employment of such means during a real-time large military operation, but also to study how changes in the perception of collective victimhood affected the level of this support. Previous studies conducted in the Israeli-Palestinian context have shown that the effect of terror on attitudes regarding peace varies according to ideological orientations and the transitional context in which terror occurs (Sharvit, Bar-Tal, Raviv, Raviv, & Gurevich, 2010). We similarly investigated the effects of context, but focusing on the different layers of collective victimhood.…”
Section: Studymentioning
confidence: 99%
“…Political left or right in the Israeli context mostly refers to the continuum between hawkish and dovish views regarding the Israeli-Palestinian conflict. This ideological orientation is associated with differential support for various political and social policies (seeSharvit, Bar-Tal, Raviv, Raviv, & Gurevich, 2010).…”
mentioning
confidence: 99%